Outcomes Of Pregnancy and Childbirth in Women with Bleeding in Early Pregnancy (Eurasian Medical Research Periodical, 2024)
Miscarriage is still a pressing problem in modern obstetrics. Despite the progress achieved in recent years in the prevention and treatment of this pathology, the frequency of spontaneous miscarriages remains quite high. So, according to various authors, it ranges from 2 to 55%. In turn, as the number of spontaneous miscarriages increases, the risk of interruption of subsequent pregnancies sharply increases